Penggunaan Metode Taguchi untuk Menentukan Kondisi Parameter Optimum Pada Pembuatan CaO dari Batu Kapur (CaCO-3) - Lilik Widia; Roniyus Marjunus; Sudibyo (Journal of Energy, Material, and Instrumentation Technology, 2021)
Research has been carried out to determine the optimum conditions for making quicklime (CaO) using the Taguchi Method. CaO is the burning result of limestone (CaC ) in calcination process by releasing of C  gas until CaO solids occur. The limestone was calcined at .  The Taguchi Method is a quality improvement technique with the selection of the most influential parameters of the making of process CaO. The parameters are particle size, CaO mass, heating temperature and stirring time. The XRF results show that the levels of CaO after the Taguchi Method design has increased from 98.779% to 98.814%. The XRD results show that the CaO phase is amorphous. The phase which were formed by calcination are Lime (CaO), Quartz (Si ) and Hematite ( ). Based on the SEM results, the morphology of CaC  has an irregular particle size and tends to be a granular solid due to the presence of impurity. Meanwhile, the results of the EDS analysis show that the content of Calcium (Ca) is quite high. From the design results of the Taguchi Method, the optimum conditions is obtained at a particle size of 140 mesh, 75 gr CaO mass, heating temperature  and stirring time 0,5 hour.